Concert and a Question of Time - Pająk, Patrycjusz (Poznańskie Studia Slawistyczne, 2017)
The focus on the structural and semantic role of time is one of the key features of modernist cinema in the period after the Second World War. Modernist filmmakers experiment with means of aesthetic expression, such as montage, mise-en-scène, camera work, which define the story time and consequently make time the subject of film story. Concert (1954) directed by Branko Belan initiates the modernist experiment with time in the Croatian feature film. Belan achieves a radical temporal discontinuity and the condensation of time thanks to extensive ellipses, expanded flashback, deep space composition, variable narrative perspective, variable position of the characters in the story and genre hybridity. In this way he specifies two dimensions of time – historical and personal. In Concert historical time does not always affect personal time that can be subjected to fate. By that means the director contests the communist belief in the positive impact of historical changes on the life of an individual.